Metabolite Profiling of Meridianin C In Vivo of Rat by UHPLC/Q-TOF MS - Guozhe Zhang; Linxia Xiao; Liang Qi (Journal of Analytical Methods in Chemistry)
Meridianin C (MC), as a marine alkaloid, is a potent protein kinase inhibitor which exhibits good anticancer activity. However, the in vivo metabolism of MC has not been described to date. In this study, an ultra-high performance liquid chromatography/quadrupole time-of-flight mass spectrometry (UHPLC/Q-TOF MS) method is employed to investigate the in vivo metabolites of MC in rats. Plasma, bile, urine, and feces are collected after a single oral dose of MC. Protein precipitation, solid phase extraction (SPE), and ultrasonic extraction methods are used to prepare samples. Based on the mass spectral fragmentation patterns, elution order, and retrieving literatures, a total of 13 metabolites of MC were detected and tentatively identified, utilizing MetaboLynx software. The metabolic pathways of MC in rats include N- or O-glucuronidation, O-sulfation, N-hydroxylation, dihydroxylation, and trihydroxylation. The relative content of the metabolites in each kinds of biological samples is also evaluated. This study will help to understand the in vivo properties of MC for the future usage.